(untitled) (Mustansiria Dental Journal, 2018)
Nickel and chromium can cause hypersensitivity in some people , this study was conducted to investigate the alteration in the nickel and chromium concentrations in saliva of patients with fixed orthodontic appliance. The investigation is comprised of 45 orthodontic patients .The selected sample divided into 3 groups. The first group consisted of 15 patients with fixed appliances in their upper & lower arches. The second group consisted of 15 patients with a fixed appliance placed only in the upper arch. The control group consisted of 15 patients who were not undergoing orthodontic treatment. Nickel and chromium release was quantified with the use of an atomic absorption spectrophotometr. The analysis of variance was used to determine if differences existed between the nickel and chromium release according to time interval. Four samples of stimulated saliva were collected from each patient before insertion of fixed appliance, 1 week , 1month , and 2month after insertion of the appliance. A considerable variation in the concentrations of both nickel and chromium was observed. Significant differences were found between the no-appliance samples and the samples obtained after insertion of the appliance. Nickel and chromium concentrations of saliva are significantly affected by fixed orthodontic appliances during the first 2 month of treatment.